Knowledge, attitude, and practices regarding COVID-19 among college-degree students in Southern district of India - Bellagolla Changalarayappa Narasimha; Sharavanan Eshwar Udayar; Kruthika Kishore Kumar; Madeshan Ashwini (Shahrekord University of Medical Sciences, 2022)
Background and aims: A case of coronavirus disease 2019 (COVID-19) was identified first in Wuhan, China in December 2019. To prevent the rampant spread of COVID-19, the behavioral change of people was crucial. This study aimed to determine the knowledge, attitude, and practice (KAP) toward COVID-19 among college-degree students in the southern district of India. Methods: A cross-sectional, online study was conducted from January to February 2021 among 400 college-degree students. Snowball sampling technique was adopted for collecting data using a semi-structured questionnaire. Data were entered in Excel and analyzed using Epi Info version 7.2. Results: Out of 400 participants, 107 (26.75%) were male and 293 (73.25%) were female. Out of all the men in the study, 107 (100%) had good knowledge regarding COVID-19 infection, whereas 276 (94.2%) of women had good and 17 (5.8%) had average knowledge (P<0.01). A total of 262 (89.4%) and 31 (10.6%) women had a positive attitude and neutral attitude toward COVID-19 infection, respectively, whereas in men, the majority (86, 80.4%) had a positive, followed by (14, 13.1%) negative and (7, 6.5%) had neutral attitude (P<0.001). All the students 400 (100%) had good practice 400 (100%) regarding COVID-19 infection. Conclusion: The male students had better knowledge about COVID-19 infection, but the positive attitude towards COVID-19 was higher among women. The practice regarding COVID-19 infection was satisfactory among all the students.